Penerapan Konsep STP dalam Manajemen Pemasaran Modern Studi Kasus Apple Inc. - Adi Setiawan Saputra; Gilang Adi Winahyu; Rizky Nasrullah; Yani Iriani (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study aims to describe the implementation of the Segmenting, Targeting, and Positioning (STP) concept in Apple Inc.’s marketing strategy and to assess students’ perceptions as young consumers of Apple products. A descriptive qualitative approach was applied through a literature review supported by an online survey involving 30 students who use Apple products. Data were analyzed descriptively to relate Apple’s STP strategy to respondent preferences and satisfaction levels. The results indicate that Apple applies multidimensional market segmentation encompassing demographic, psychographic, and behavioral aspects, targeting premium consumers, creative professionals, and urban youth. The targeting strategy emphasizes product quality, design, and symbolic value, while positioning is established as a premium brand supported by an integrated product ecosystem. Survey findings show that ease of access is the most prioritized factor among respondents (40%), followed by information completeness (33%). The overall satisfaction level is categorized as moderate, with a mean score of 3.67. These findings suggest that Apple’s STP strategy has been effective in strengthening brand image among students; however, improvements are still needed, particularly in information delivery and service accessibility. This study is expected to provide practical insights for businesses and educational institutions in developing marketing strategies aligned with young consumer characteristics.